Knowledge about Coronavirus disease 19 (COVID-19) and its professional repercussions among Brazilian endodontists - George Táccio de Miranda CANDEIRO; Giulio GAVINI; Rodrigo Ricci VIVAN; Bruna Marjorie Dias Frota CARVALHO; Marco Antônio Húngaro DUARTE; Camila Pontes FEIJÃO; Camila Pontes FEIJÃO (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of this study was to assess Brazilian endodontists' level of knowledge about the coronavirus disease (COVID-19) and examine its professional repercussions. The link to the online survey that was created for this study was shared with Brazilian endodontists through social networking applications. The questionnaire contained questions that pertained to COVID-19 and its impact on dental practice. The collected data were analyzed using t-test, chi-square analysis, and analysis of variance, and the level of significance was set at 0.05. A total of 2,135 participants responded to the questionnaire, and all five Brazilian regions were represented in the sample. A total of 98.50% of endodontists reported that dental procedures can transmit COVID-19. Complete social distancing was practiced by 96.68% of the participants, and approximately 25% knew someone who had COVID-19. Moreover, in their daily practice, 72.13% of them implemented biosecurity measures that are ineffective in preventing COVID-19. Furthermore, 91.7% of them reportedly suspended elective dental procedures. Only 55.69% of them reported that they performed only emergency procedures in their workplaces. Those who believed that COVID-19 cannot be transmitted during dental procedures were less knowledgeable about the symptoms of COVID-19 (p = 0.0095). Endodontists who believed that personal protective equipment cannot prevent contamination were more knowledgeable about the symptoms of COVID-19 than their counterparts (p = 0.0003). The participating Brazilian endodontists demonstrated adequate knowledge about the risk of contamination during dental procedures and the main symptoms of COVID-19. Only some professionals reported providing emergency dental care during the pandemic.